Have e-cigarettes renormalised or displaced youth smoking? Results of a segmented regression analysis of repeated cross sectional survey data in England, Scotland and Wales. Issue 2 (1st April 2019) - Hallingberg, Britt; Maynard, Olivia M; Bauld, Linda; Brown, Rachel; Gray, Linsay; Lowthian, Emily; MacKintosh, Anne-Marie; Moore, Laurence; Munafo, Marcus R; Moore, Graham
Abstract : Objectives: To examine whether during a period of limited e-cigarette regulation and rapid growth in their use, smoking began to become renormalised among young people. Design: Interrupted time-series analysis of repeated cross-sectional time-series data. Setting: Great Britain Participants: 248 324 young people aged approximately 13 and 15 years, from three national surveys during the years 1998–2015. Intervention: Unregulated growth of e-cigarette use (following the year 2010, until 2015). Outcome measures: Primary outcomes were prevalence of self-reported ever smoking and regular smoking. Secondary outcomes were attitudes towards smoking. Tertiary outcomes were ever use of cannabis and alcohol. Results: In final models, no significant change was detected in the pre-existing trend for ever smoking (OR 1.01, CI 0.99 to 1.03). There was a marginally significant slowing in the rate of decline for regular smoking (OR 1.04, CI 1.00 to 1.08), accompanied by a larger slowing in the rate of decline of cannabis use (OR 1.21, CI 1.18 to 1.25) and alcohol use (OR 1.17, CI 1.14 to 1.19). In all models and subgroup analyses for smoking attitudes, an increased rate of decline was observed after 2010 (OR 0.88, CI 0.86 to 0.90). Models were robust to sensitivity analyses. Conclusions: There was a marginal slowing in the decline in regular smoking during the period following 2010, when e-cigarettes were emerging but relatively unregulated. However, these patterns were not unique to tobacco use and the decline in the acceptability of smoking behaviour among youth accelerated during this time. These analyses provide little evidence that renormalisation of youth smoking was occurring during a period of rapid growth and limited regulation of e-cigarettes from 2011 to 2015. Trial registration number: Research registry number: researchregistry4336